Nanofluid heat transfer under mixed convection flow in a tube for solar thermal energy applications - Sekhar, Y.R. (Springer Verlag, 2016)
The solar flat plate collector operating under different convective modes has low efficiency for energy conversion. The energy absorbed by the working fluid in the collector system and its heat transfer characteristics vary with solar insolation and mass flow rate. The performance of the system is improved by reducing the losses from the collector. Various passive methods have been devised to aid energy absorption by the working fluid. Also, working fluids are modified using nanoparticles to improve the thermal properties of the fluid. In the present work, simulation and experimental studies are undertaken for pipe flow at constant heat flux boundary condition in the mixed convection mode. The working fluid at low Reynolds number in the mixed laminar flow range is undertaken with water in thermosyphon mode for different inclination angles of the tube. Local and average coefficients are determined experimentally and compared with theoretical values for water-based Al2O3 nanofluids. The results show an enhancement in heat transfer in the experimental range with Rayleigh number at higher inclinations of the collector tube for water and nanofluids. Â© 2015, Springer-Verlag Berlin Heidelberg.